2023
DOI: 10.1371/journal.pone.0287992
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma infection and Rhesus blood group system: A systematic review and meta-analysis

Abstract: Background Toxoplasmosis is one of the most common infections in humans and animals, which is caused by an obligate intracellular opportunistic parasite known as Toxoplasma gondii (T. gondii). Some data have shown that both Rhesus (Rh)-positive and Rh-negative individuals differ in response to biological factors, including Toxoplasma infection. Therefore, this systematic review and meta-analysis was conducted to investigate the scientific evidence regarding the possible association between the Rh blood group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…However, our results agree with those reported in a meta-analysis that included 10,910 people of 21 studies and showed that no significant association was found between anti- T. gondii antibodies and Rh blood group [ 24 ]. In such meta-analysis researchers studied individuals of 3 continents including Asia, Europe and Africa but there was no available data on America and Australia [ 26 ]. Blood group systems other than the ABO system have been assessed on their association with T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results agree with those reported in a meta-analysis that included 10,910 people of 21 studies and showed that no significant association was found between anti- T. gondii antibodies and Rh blood group [ 24 ]. In such meta-analysis researchers studied individuals of 3 continents including Asia, Europe and Africa but there was no available data on America and Australia [ 26 ]. Blood group systems other than the ABO system have been assessed on their association with T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…In other hand, higher testosterone levels in infected males may result to higher psychoticism and interpersonal sensitivity symptoms than non‐infected men [34, 68, 75]. Psychoticism was defined by Hans Eysenck, a German–British psychologist, as a personality type that is prone to take risks, might engage in anti‐social behaviours, impulsiveness or non‐conformist behaviour.…”
Section: Immunological Neurological Psychological and Behavioural Eff...mentioning
confidence: 99%
“…However, they may also exhibit a diminished responsiveness to motivational rewards, potentially due to an elevation in dopamine levels [85]. It is noteworthy that there is evidence indicating some behavioural personality traits differ between infected women and men [2, 72, 75, 83].…”
Section: Immunological Neurological Psychological and Behavioural Eff...mentioning
confidence: 99%
See 2 more Smart Citations